Examining the Application and Effectiveness of Behaviorists Learning Theories in Teaching and Learning Process - Kyauta, Amadu Muktar A.; Bulama, Asheik; Maiwada, Bashir Lawal (NIU Journal of Social Sciences, 2018)
This paper attempted to examine the application and effectiveness of behaviorist learning theories in teaching and learning process. That is classical conditioning learning theory by Ivan Pavlov and operant conditioning learning theory by B. F Skinner. Learning is a process by which experience and practice produce relatively stable or permanent changes in an organismâ€™s behavior and capabilities. Learning is a key process in human behavior and it start from birth to the end of life. It pervades everything we do and think. It plays a central role in the language we speak, our personality traits, attitudes and beliefs. A theory is an attempt to organize and integrate knowledge to explain why things happen the way they do. It can as well mean a set of assumption or postulates that state the basis or the premise of the field with which the theory is concerned on. Learning theories, on the other hand, are conceptual frameworks that describe how information is absorbed, processed, and retained during learning. It brings together cognitive, emotional, and environmental influences and experiences for acquiring, enhancing, or making changes in oneâ€™s knowledge, skills and values. Behaviorists learning theorist is very effective when applied appropriately in teaching and learning situation. It equips the teachers with various teaching methods and strategies, it also helps them on how to use teaching aid, how to reinforce students and motivate them to learn etc. Keywords:   Behaviorists Learning Theorist Teaching Learning Process.